2010
DOI: 10.1111/j.1365-2222.2010.03557.x
|View full text |Cite
|
Sign up to set email alerts
|

British Society for Allergy and Clinical Immunology guidelines for the management of egg allergy

Abstract: SummaryThis guideline advises on the management of patients with egg allergy. Most commonly, egg allergy presents in infancy, with a prevalence of approximately 2% in children and 0.1% in adults. A clear clinical history and the detection of egg white-specific IgE (by skin prick test or serum assay) will confirm the diagnosis in most cases. Egg avoidance advice is the cornerstone of management. Egg allergy often resolves and re-introduction can be achieved at home if reactions have been mild and there is no as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 53 publications
1
82
0
6
Order By: Relevance
“…At present, there is no national guideline for the management of children with food allergies, other than the guideline on egg allergy from the British Society for Allergy and Clinical Immunology. 2 As such, the management of children diagnosed with food allergy will continue to be variable. The NICE guideline presents a challenge to the current primary care diagnosis of food allergy in children and young people.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no national guideline for the management of children with food allergies, other than the guideline on egg allergy from the British Society for Allergy and Clinical Immunology. 2 As such, the management of children diagnosed with food allergy will continue to be variable. The NICE guideline presents a challenge to the current primary care diagnosis of food allergy in children and young people.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, studies have shown that children with egg allergy are vaccinated in a single dose, in 2 divided doses, or with a graded dose increase (19 (23,24). Among those administered divided vaccination at equal doses, we found doubtful rashes in one patient who underwent only measles vaccination in our clinic, but we did not have any systemic findings.…”
Section: Discussionmentioning
confidence: 99%
“…If there was a suspicious rash, the patient was called in the following days and was followed up for 1-2 days. The vaccine application for those having egg allergy has been adapted from the protocol of influenza vaccination (2010 BSACI) in such patients (19).…”
Section: Application Protocol Of Vaccinesmentioning
confidence: 99%
“…In young children food allergy can present as a food aversion due to underlying symptoms of lip tingling, abdominal pain or nausea, which non-verbal child cannot express. In very young children severe reactions can present as paleness and floppiness due to underlying cardiovascular compromise (11). Depending on the child's age, irritability, reduced activity or sudden change in behaviour, can be one of the first manifestations of developing a reaction and therefore detailed history taking during assessment and, in acute circumstances, careful observation is paramount.…”
Section: Symptomsmentioning
confidence: 99%
“…ImmunoCAP, Phadia, ThermoFisher Scientific, Sweden). Although the presence of positive skin prick test response or detection of serum sIgE antibodies does not always accurately predict if the child has an allergy, generally the likelihood of clinical allergy correlates with the size of the SPT weal and the level of sIgE (11)(12)(13). If indicated, as in cases where there is no clear history of allergic reaction on exposure to suspect food, OFC are considered a gold standard for diagnosing food allergy (1,12).…”
Section: Diagnosismentioning
confidence: 99%